Evaluation of phosphorus adsorption capacity of various filter materials from aqueous solution - Adhikari, R.; Krishna, K.; Sarukkalige, Priyantha Ranjan (SAGE PUBLICATIONS INC, 2016)
Rapid urbanisation has significantly increased the impervious surface along with increase in pollutants such as nutrients (nitrogen, phosphorus), sediments, oil, and hydrocarbon in stormwater. Their removal is important as they adversely affect the aquatic ecosystem and the environment.Thus, this study evaluated the performance of various adsorbent materials (red gum mulch, pine mulch, flyash, oyster shell, sawdust, clay, sand, zeolite, dolomite, alum and lime sludges) for the removal of phosphorus from synthetic stormwater. Among them, alum and lime sludges appeared to be the most effective in removing phosphorus. Further analysis showed that alum and lime sludges remove 99 and 90% phosphorus within 60minutes from the synthetic stormwater. Therefore, this study demonstrates that the lime and alum sludges could be highly useful as a sustainable and cheap filter media for stormwater treatment systems that are enriched in phosphorus.